Evaluation of asphaltene-induced formation damage around the near wellbore region - Elochukwu, Okafor Henry (2013)
Asphaltene are organic deposits which are originally in solution or colloidal suspension in the crude oil. Due to changes in the crude oil composition, temperature and pressure, asphaltene precipitates into distinctive solid phase, after which it flocculates and deposit on rock surfaces and pores. Asphaltene deposition in the porous media causes damage to the formation. To evaluate formation damage due to asphaltene deposition, a computer program is developed to evaluate parametres such as permeability, porosity, skin factor and pressure within the damage region. Results from the evaluation indicates that asphaltene-induced formation damage is severe at the wellbore and less severe away from the wellbore. Analyzing the profiles generated from computer program for three scenarios; at the wellbore (0.29ft), near the wellbore (1ft) and away from the wellbore (10ft). Results indicate that the effect of asphaltene deposition is less severe as the radial distance approaches the radius of asphaltene flocculation. The effect of flow rate on the severity of formation damage is studied using the developed computer program. It is observed that for an increased flow rate (4000 bbl/day, 4200 bbl/day and 4500 bbl/day), asphaltene-induced formation damage is severe at the wellbore but at a reduced flow rate (3000 bbl/day and 2000 bbl/day), the severity of the damage is low thereby prolonging the production time prior to severe formation damage.